Global Perspectives on War-Induced Migration : Analyzing Drivers, Impacts, and Policy Responses - Shyshmintsev, Andrii; Shymanska, Kateryna; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis examines the causes of forced migration triggered by war, political instability, and security concerns in the context of contemporary conflicts—namely, the Ukraine–Russia war, the Syrian civil war, the Israel–Palestine conflict, and the war in Afghanistan. The study specifically focuses on the socio-economic impacts of such migration on host countries, particularly examining effects on labor markets, economic structures, and social integration. In addition, the thesis evaluates current policy responses implemented by host countries to manage and mitigate the consequences of large-scale forced displacement.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses